ADSORPTION OF Cu (II) FOR PEARLS CALCIUM ALGINAT WITH PARTICLE TRAPPED OF Lessonia Trabeculata - Tapia, Nelson (2007)
lt has been obtained bead of calcium alginate with micro-particles of algae Lessonia Trabeculata. The optimum pH for adsorption of Cu(II) lie between 4.5 and 5. From the study of the kinetics of adsorption was determined that the thermodynamic equilibrium was reached alter 500min. The adsorption data fitted well with the Langmuir model and showed the maximum adsorption capacity q max =14,66mg/g.